Establishment and Verification of Neural Network for Rapid and Accurate Cytological Examination of Four Types of Cerebrospinal Fluid Cells - Jiang, Luyue; Niu, Gang; Liu, Yangyang; Yu, Wenjin; Wu, Heping; Xie, Zhen; Ren, Matthew Xinhu; Quan, Yi; Jiang, Zhuangde; Zhao, Gang; Ren, Wei (Frontiers in Medicine, 2022)
Fast and accurate cerebrospinal fluid cytology is the key to the diagnosis of many central nervous system diseases. However, in actual clinical work, cytological counting and classification of cerebrospinal fluid are often time-consuming and prone to human error. In this report, we have developed a deep neural network (DNN) for cell counting and classification of cerebrospinal fluid cytology. The May-Grüwald Giemsa (MGG) stained image is annotated and input into the DNN network. The main cell types include: lymphocytes, monocytes, neutrophils and red blood cells. In clinical practice, the use of DNN is compared with the results of expert examinations in the professional cerebrospinal fluid room of a First-line 3A Hospital. The results show that the report produced by the DNN network is more accurate, with an accuracy of 95% and a reduction in turnaround time by 86%. This study shows the feasibility of applying DNN to clinical cerebrospinal fluid cytology.